Knockout of α-calcitonin gene-related peptide attenuates cholestatic liver injury by differentially regulating cellular senescence of hepatic stellate cells and cholangiocytes - Wan, Ying (Lab Invest, 2019)
BACKGROUND: α-Calcitonin gene-related peptide (α-CGRP) is a 37-amino acid neuropeptide involved in several pathophysiological processes. α-CGRP is involved in the regulation of cholangiocyte proliferation during cholestasis. In this study, we aimed to evaluate if α-CGRP regulates bile duct ligation (BDL)-induced liver fibrosis by using a α-CGRP knockout (α-CGRP(−/−)) mouse model. METHODS: α-CGRP(−/−) and wild-type (WT) mice were subjected to sham surgery or BDL for 7 days. Then, liver fibrosis and cellular senescence as well as the expression of kinase such as p38 and C-Jun N-terminal protein kinase (JNK) in mitogen-activated protein kinases (MAPK) signaling pathway were evaluated in total liver, together with measurement of cellular senescence in cholangiocytes or hepatic stellate cells (HSCs). RESULTS: There was enhanced hepatic expression of Calca (coding α-CGRP) and the CGRP-receptor components (CRLR, RAMP-1 and RCP) in BDL and in both WT α-CGRP(−/−) and BDL α-CGRP(−/−) mice, respectively. Moreover, there was increased CGRP serum levels and hepatic mRNA expression of CALCA and CGRP receptor components in late-stage PSC samples compared to healthy control samples. Depletion of α-CGRP reduced liver injury and fibrosis in BDL mice that was associated with enhanced cellular senescence of hepatic stellate cells and reduced senescence of cholangiocytes as well as decreased activation of p38 and JNK MAPK signaling pathway. Cholangiocyte supernatant from BDL α-CGRP(−/−) mice inhibited the activation and increased cellular senescence of cultured human HSCs (HHSCs) compared to HHSCs stimulated with BDL cholangiocyte supernatant. Taken together, endogenous α-CGRP promoted BDL-induced cholestatic liver fibrosis through differential changes in senescence of HSCs and cholangiocytes and activation of p38 and JNK signaling. Modulation of α-CGRP/CGRP receptor signaling may be key for the management of biliary senescence and liver fibrosis in cholangiopathies.